Leishmanicidal activities of Artemisia annua leaf essential oil against Visceral Leishmaniasis - Islamuddin, Mohammad; Chouhan, Garima; Want, Muzamil Y.; Tyagi, Maujiram; Abdin, Malik Z.; Sahal, Dinkar; Afrin, Farhat (Frontiers in Microbiology, 2014)
Visceral leishmaniasis (VL), the second-most dreaded parasitic disease after malaria, is currently endemic in 88 countries. Dramatic increases in the rates of infection, drug resistance and non-availability of safe vaccines have highlighted the need for identification of novel and inexpensive anti-leishmanial agents from natural sources. In this study, we showed the leishmanicidal effect of essential oil from Artemisia annua leaves (AALEO) against Leishmania donovani in vitro and in vivo. AALEO was extracted by hydrodistillation and characterized by GC-MS, the most abundant compounds were found to be camphor (52.06 %) followed by β-caryophyllene (10.95 %). AALEO exhibited significant leishmanicidal activity against L. donovani, with 50 % inhibitory concentration of 14.63 ± 1.49 µg ml-1 and 7.3 ± 1.85 µg ml─1, respectively, against the promastigotes and intracellular amastigotes. The effect was mediated through programmed cell death as confirmed by externalization of phosphatidylserine, DNA nicking by TdT-mediated dUTP nick-end labelling (TUNEL) assay, dyskinetoplastidy, cell cycle arrest at sub-G0–G1 phase, loss of mitochondrial membrane potential and reactive oxygen species (ROS) generation in promastigotes and nitric oxide (NO) generation in ex vivo model. AALEO presented no cytotoxic effects against mammalian macrophages even at 200 µg ml─1. Intra-peritoneal administration of AALEO (200 mg/ kg.b.w.) to infected BALB/c mice reduced the parasite burden by almost 90 % in the liver and spleen with significant reduction in weight. There was no hepato- or nephro-toxicity as demonstrated by normal levels of serum enzymes. The promising antileishmanial activity shown by camphor-rich AALEO may provide a new lead in the treatment of VL.